2017
DOI: 10.1002/per.2102
|View full text |Cite
|
Sign up to set email alerts
|

Does A Major Earthquake Change Job Preferences and Human Values?

Abstract: Does a major natural disaster change human values and job preferences? The present studies examined whether the experience of a natural disaster experience shifts people's values and job preferences toward pro‐social directions. In Study 1 (cross‐temporal analysis), we analysed job application data in nine cities in Japan over 12 years and found that the popularity of pro‐social occupations (e.g. firefighter) increased after the Great Hanshin–Awaji Earthquake in 1995, in particular the area hit hardest by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 42 publications
3
36
0
Order By: Relevance
“…There were too few observations available for natural disasters to be credibly compared to other ecological predictors of democracy in the present longitudinal analyses. Alternative frameworks such as regression discontinuity may be more appropriate to capture the abrupt characteristic of disaster occurrences [63]. Nonetheless, our comprehensive analyses show that even when natural disasters are conceptualized as a historical variable at the country level, they play only a minor role in affecting democracy compared to economic wealth and pathogen prevalence.…”
Section: Natural Disaster Casualtiesmentioning
confidence: 95%
“…There were too few observations available for natural disasters to be credibly compared to other ecological predictors of democracy in the present longitudinal analyses. Alternative frameworks such as regression discontinuity may be more appropriate to capture the abrupt characteristic of disaster occurrences [63]. Nonetheless, our comprehensive analyses show that even when natural disasters are conceptualized as a historical variable at the country level, they play only a minor role in affecting democracy compared to economic wealth and pathogen prevalence.…”
Section: Natural Disaster Casualtiesmentioning
confidence: 95%
“…Third, the present research is cross-sectional, thus limiting causal implications of ecological threats. A longitudinal approach is more suitable for identifying societal changes due to ecological conditions than exploring country variations (Oishi et al, 2017 ; Varnum and Grossmann, 2017 ). Fourth, we did not scrutinize validity of some of the variables tested in the present study (e.g., historic pathogen prevalence).…”
Section: Limitations Of the Present Studymentioning
confidence: 99%
“…Previous research from this approach demonstrated that natural disaster risk was associated with higher levels of collectivism (Oishi and Komiya, 2017 ). Other work inspired by the socio-ecological approach found that prosocial values and behaviors significantly increased after major earthquake incidents in Japan (Oishi et al, 2017 ). This line of research assumes that natural disasters bring people together, or enhance collectivistic values, to mitigate the consequences of natural disasters.…”
Section: Introductionmentioning
confidence: 99%
“…Humans have always had to deal with them. Recent research suggests that natural disasters and pandemics have shaped human values, norms, and culture (Gelfand et al, 2011;Oishi et al, 2017;Schaller & Murray, 2008;Van de Vliert, 2013). Recent research also shows that natural disasters and pandemics affect racial minority and lower socioeconomic status individuals disproportionately (e.g., Rhodes et al, 2010;Stephens et al, 2009;Yamada, 2009).…”
mentioning
confidence: 99%